2008
DOI: 10.1177/002182860803900203
|View full text |Cite
|
Sign up to set email alerts
|

On the Orientation of Ancient Egyptian Temples: (4) Epilogue in Serabit El Khadim and Overview

Abstract: During the last four years, the Egyptian-Spanish Mission on Egyptian Archaeoastronomy, conducted under the auspices of the Egyptian Supreme Council of Antiquities, has been carrying out an ambitious scientific project with the aim of studying the cosmovision of the ancient civilization of the pharaohs. Part of the project consists of a re-analysis of the iconographic and historical sources that has allowed, among other things, a reassessment of the calendar theory, 1 a challenge to old fashioned paradigms, 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, it is now sure that the ancient Egyptians orientated their monuments and sacred buildings toward the rising points of some bright stars, such as Sirius and Canopus, and that they used other stars (namely those of the constellation Ursa Major, or the Big Bear) to align temples and pyramids with the cardinal points (see Belmonte, Shaltout, & Fekri, 2008, and references therein).…”
mentioning
confidence: 99%
“…Furthermore, it is now sure that the ancient Egyptians orientated their monuments and sacred buildings toward the rising points of some bright stars, such as Sirius and Canopus, and that they used other stars (namely those of the constellation Ursa Major, or the Big Bear) to align temples and pyramids with the cardinal points (see Belmonte, Shaltout, & Fekri, 2008, and references therein).…”
mentioning
confidence: 99%
“…10 C. L. N. Ruggles with the sun, moon or stars. The more recent work of Belmonte and his colleagues in their surveys of some 330 alignments at Egyptian temples and pyramids (Belmonte et al 2008;Belmonte & Shaltout 2009) also provides clear testimony to the success and value of such an approach.…”
Section: Data-driven and Onwardmentioning
confidence: 95%
“…31 Moreover, by embodying such an alignment, the temple was also perpendicular to the local course of the Nile. 32 The texts have shown that the Feast of Amun of Gematen was celebrated in Kawa on I Ahket 1, commemorating the inauguration of the temple in Wepet Renpet c. 680 B.C. 33 At that epoch, the declination of the sun was of the order of -16¾º.…”
Section: Orienting the Amun Yemplesmentioning
confidence: 99%